The Role of Routine Practice in Healthcare Worker Strategies when Doffing Unfamiliar Personal Protective Equipment. (October 2020) - Chasco, Emily; Silva, Jaqueline Pereira da; Dukes, Kimberly; Baloh, Jure; Ward, Melissa; Salehi, Hugh; Reisinger, Heather; Pennathur, Priyadarshini; Abbott, Loreen Herwaldt
Abstract : Background: Appropriate doffing of personal protective equipment (PPE) prevents healthcare worker (HCW) self-contamination and spread of pathogens. HCWs may encounter an array of PPE types (eg, gloves, gowns, masks) and designs (eg, masks with elastic ear loops vs ties) during their duties, some of which may be unfamiliar. We know little about how HCWs strategize when doffing unfamiliar PPE. As part of a larger study examining the doffing process and the risk of self-contamination, we used qualitative methods to explore factors influencing HCW PPE doffing strategies. Methods: In total, 70 HCW participants from 2 Midwestern academic hospitals were assigned to 1 of 4 doffing simulation scenarios. In the first 3 scenarios, participants were asked to doff 3 mask designs (n = 10), 2 gown designs (n = 10), or 2 glove designs (n = 10). In the fourth scenario, HCWs with different levels of training (n = 40) participated in 2 doffing simulations randomized per participant: a distraction simulation and a nondistraction simulation (using identical PPE types and designs). In all scenarios, participants were instructed to doff in their usual manner. Doffing performances were video-recorded. Participants then reviewed the recordings and took part in short semistructured interviews about their performance. Interviews were audio-recorded, transcribed, and analyzed using thematic analysis. Results: When faced with unfamiliar PPE during the simulations, participants were required to problem solve. In so doing, participants reported drawing on their day-to-day routine practices with familiar PPE to inform their doffing strategies. Aspects of routine practice identified as influential included PPE types typically worn, PPE donning and doffing order, doffing frequency, familiar PPE design cues, and experience tailoring strategies to specific patient care contexts. Participants frequently reported the desire to avoid self-contamination as driving doffing strategies and problem solving, but they also noted unique patient care demands related to their specific roles when they explained their doffing decisions. At the same time, HCWs identified lack of familiarity, lack of training, and nonintuitive design as barriers to doffing appropriately when encountering unfamiliar PPE. Conclusions: Different PPE designs may not be interchangeable, and proper doffing techniques may not be intuitive. The previous experiences of HCWs informed their strategies when doffing unfamiliar PPE. However, this practice sometimes caused them to use inappropriate doffing techniques and resulted in self-contamination. This finding has important implications for hospital policies and procedures regarding the introduction of new PPE and indicates that HCWs need training when new items are introduced. Funding: None Disclosures: None